Analysis Financial Distress With Good Corporate Governance As A Moderating Variable In Transportation And Logistics Companies On The Indonesia Stock Exchange - Mahabbah, Hasna Inayah Nur; Nur, Dhani Ichsanuddin (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the effect of leverage, firm size, and investment decisions on financial distress with GCG as a moderating variable in the transportation and logistics sector on the Indonesia Stock Exchange for the period 2020-2023. This research uses quantitative methods with Moderated Regression Analysis techniques. The research population is transportation and logistics sector on the Indonesia Stock Exchange for the period 2020-2023 with a sample of 56 through purposive sampling technique. The results state that leverage does not contribute to financial distress, firm size contributes to financial distress, and investment decisions do not contribute to financial distress. GCG increases the relationship between firm size and financial distress, but GCG cannot moderate the relationship between leverage and financial distress and GCG is unable to moderate the relationship between investment decisions and financial distress. This research suggests that companies manage assets appropriately and implement good corporate governance to ensure asset control.